Implementasi Media Pembelajaran Pengenalan Jenis Kapal - Muhammad Hamidi; Yudi Yudi; Muhammad Fauzi (Cybernetics: Journal Educational Research and Social Studies, 2023)
Ships are water vehicles of a certain type and shape that transport passengers and goods through waters to certain areas. Say, for example, like crossing islands, delivering goods by sea, or being used as a component in a floating market. Ships are included in the learning category for the Belawan Maritime Academy campus in Medan for cadets, therefore the author applies this material to learning media bases of flash for better delivery of material. For better learning implementation results and in accordance with ship specifications, references are used by tracing data from journals and the internet, the system uses a waterfall for data collection techniques so that later the learning media is validated for its truth with clear data references. This system can be implemented in a learning system with PC or laptop devices as the medium and used as learning material for cadets. With this application, it is hoped that cadets will find it easier to study ships in more depth and can be re-developed into a better system.